Hardware block for use in programmable microwave function arrays. Issue 15 (1st July 2014) - Kelly, J.R.; Borja, A.L.
Abstract : Ultimately, the research presented will lead to the development of a microwave integrated circuit that is analogous to a field programmable gate array. An early step towards the development of this technology is presented. Specifically, a 3‐port device, based on a single resonant element, namely a microstrip square patch, is described. The device operates simultaneously as a filter and an antenna. Filter performance is obtained between ports 1 and 2. Antenna performance is obtained on port 3.